Data mining algorithms 1 - Witten, Ian (Henry Stewart Talks, 2008)
Simplicity first, One attribute does all the work, Complications: missing values, Overfitting, Evaluating the result, Description of the method, Statistical modeling, Bayes's rule, Weather data: probabilities, Zero frequencies, missing values, Numeric attributes, "Naive" statistical model, Constructing decision trees, Continuing to split, Highly-branching attributes, Overfitting and the need to prune, Constructing rules, Rules versus trees, General algorithm, Association rules
Archived at 2022/03/17